Peran Lembaga Dakwah SC Arriyadhoh dalam character building mahasiswa - Amri Rahman (Seminar Nasional LP2M UNM, 2019)
Character building on campus can be done through well-organized and sustainable da'wah activities. The Campus Da'wah Institution (LDK) needs to play an active role as a moral movement that calls for a humanitarian civilization based on universal values of the divine revelation. This study aims to determine the role of SC Arriyadhoh da'wah institutions in building the character of UNM FIK students. This type of research is qualitative with a descriptive approach, the sample technique used is purposive sampling, the sample in this study is SC Arriyadhoh administrators, data collection techniques carried out through observation, interviews and documentation with data analysis techniques are descriptive qualitative data analysis techniques. The results of the study show that SC Arriyadhoh as a missionary organization FIK UNM plays an active role in building the character of FIK UNM students through various da'wah activities. The pattern of guidance carried out by SC Arriyadhoh FIK UNM in the development of the character of the UNM FIK students includes; the pattern of recitation in the form of khalaqah, making syiar events, such as ta'lim, tabligh, outbound, studies, sports together. SC Arriyadhoh in making efforts to build the character of FIK UNM students gets support from the campus bureaucracy both morally and materially. However, there are not a few challenges faced, including the lack of enthusiasm of students to be involved in the management of campus da'wah institutions and other constraints on funding limitations in carrying out work programs.